Review on Electrospun Conductive Polymer Composites Strain Sensors - Wang, Xin; Gao, Qingsen; Schubert, Dirk W.; Liu, Xianhu (Advanced Materials Technologies, 2023)
The rapid development of wearable smart devices with the ability to detect physiological activity has contributed to a huge demand for smart strain sensors. However, conventional strain sensors have significant limitations about stretchability. Electrospun strain sensors show great potential for application in the field of wearable strain sensors due to their light weight, good elasticity, stretchability, and ease of processing. In this review, the effects of materials, processing methods, and microstructures of electrospun strain sensors from conductive polymer composites on wearable strain sensors are summarized and discussed. The purpose of this review is to critically review the progress of electrospinning process-based strain sensors and to predict promising future directions.
CRIS-Team Scopus Importer:2023-04-21
Keywords: electrospun technology; health monitoring; intelligent electronic devices; wearable strain sensors